Memelihara Kesatuan Dalam Keragaman Gereja Berdasarkan Kitab 1 Korintus 12:12-14 dan Relevansinya Pada Hubungan Oikumenis Antar Gereja Di Tapanuli Utara - Suan Dame Siahaan (Institut Agama kristen Negeri Tarutung, 2021)
Abstract: This study aims to determine: 1. The concept of maintaining unity in the diversity of the church according to the meaning of one body based on the exegetical study of 1 Corinthians 12: 12-14. 2. The concept of unity in the diversity of the church according to the Bible – believers today. 3. Theological and practical reflection on maintaining unity in church diversity in relation to Ecumenical relations between churches in North Tapanuli. The research uses a biblical study approach, through exegesis research methods. Through this exegetical study, the author will analyze how the concept of unity in the diversity of the church according to Paul's perspective in the Bible text of 1 Corinthians 12: 12-14. Then to further sharpen theological reflection and praxis, the author will use steps to collect data from interviews, observations (field notes) and documentation.The conclusions obtained from writing this thesis are: First, the conclusion of the theological implications of the results of exegesis based on 1 Corinthians 12:12-14, emphasizes that there are two things that are needed to maintain unity in church diversity, namely 1. Awareness of self-identity. 2. Faith growth. Through it the church becomes one community as there is only one God, one body even though there are many members. This unity can be seen in sincere respect for other members of the congregation, awareness called by one God to carry out one mission, through the concept of mutual acceptance, mutual recognition, mutual support and sharing. This theological concept is the basis for the unity of the body in the diversity of the church. Second, the conclusion of the implications of parksis from the results of this thesis research interview is that 1. Ecumenical commitment must begin with awareness of one's own identity. 2. Ecumenism is not only structural, not only functional, but together in carrying out missions based on one vision. 3. The church must be able to form ecumenical relations within the framework of mutual recognition and acceptance between churches. 4. The church must form an ecumenical relationship within the framework of a ministry partnership between churches and live holy lives as the body of Christ.Keywords: Maintaining, Unity, Diversity, Church, Ecumenical Abstrak: Penelitian ini bertujuan untuk mengetahui: 1. Konsep memelihara kesatuan dalam keberagaman gereja sesuai dengan arti satu tubuh berdasarkan studi eksegetis 1 Korintus 12 : 12-14. 2. Konsep kesatuan dalam keberagaman gereja menurut Alkitab – orang percaya masa kini. 3. Refleksi teologis dan praksis tentang memelihara kesatuan dalam keragaman gereja dalam kaitannya dengan hubungan Oikumenis antar Gereja di Tapanuli Utara. Penelitian menggunakan pendekatan kajian biblika, melalui metode penelitian eksegesis. Melalui kajian Eksegetis ini penulis akan menganalisis bagaimana konsep kesatuan dalam keragaman gereja menurut perspektif Paulus dalam naskah Alkitab Surat 1 Korintus 12 : 12-14. Kemudian untuk lebih mempertajam refleksi teologis dan praksis, penulis akan menggunakan langkah-langkah pengumpulan data dari hasil wawancara, observasi (catatan lapangan) dan dokumentasi. Kesimpulan yang diperoleh dari penulisan tesis ini adalah : Pertama, Adapun kesimpulan implikasi teologis dari hasil eksegesis berdasarkan 1 Korintus 12:12-14, menekankan adanya dua hal yang diperlukan untuk memelihara kesatuan dalam keberagaman gereja yaitu 1. Kesadaran akan identitas diri. 2. Pertumbuhan iman. Melalui itu gereja menjadi satu persekutuan sebagaimana hanya ada satu Tuhan, satu tubuh walau banyak anggota. Kesatuan itu nampak pada penghormatan yang tulus kepada orang jemaat lain, kesadaran dipanggil oleh Tuhan yang satu untuk melaksanakan misi yang satu, melalui konsep saling menerima, saling mengakui, saling menopang dan saling berbagi. Konsep teologis ini merupakan dasar bagi kesatuan tubuh dalam keragaman gereja. Kedua, Adapun yang menjadi kesimpulan implikasi parksis dari hasil wawancara penelitian tesis ini adalah, bahwa 1. Komitmen oikumenis harus diawali dengan kesadaran identitas sendiri. 2. Oikumene bukan Cuma struktural, bukan cuma fungsional, tetapi kebersamaan melaksanakan misi berdasarkan visi yang satu. 3. Gereja harus mampu membentuk hubungan oikumenis dalam bingkai saling mengakui dan menerima antar gereja. 4. Gereja harus membentuk hubungan oikumenis dalam bingkai kemitraan pelayanan antar gereja dan hidup kudus sebagai tubuh Kristus.Kata Kunci: Memelihara, Kesatuan, Keragaman, Gereja, Oikumenis